2015
DOI: 10.1016/j.drugalcdep.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of major depression and nonmedical use of prescription opioids in the United States

Abstract: Introduction Recent epidemiologic studies have shown that nonmedical use of prescription opioids (NMUPO) and major depression frequently co-occur. Comorbid forms of drug use and mental illness such as NMUPO and depression pose a greater disease burden than either condition alone. However, sociodemographic and substance use differences between individuals with either NMUPO or depression and those with comorbid conditions have not yet been fully investigated. Methods Data came from the 2011 and 2012 National S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 32 publications
(44 reference statements)
6
19
0
Order By: Relevance
“…However, consistent with the findings of the recent literature examined, we found that women were more likely to report use of prescription opioids compared to men. In accordance with findings from LeResche et al, and Fink et al, we also found that women were more likely to report chronic health conditions including pain (17) and depression (14). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, consistent with the findings of the recent literature examined, we found that women were more likely to report use of prescription opioids compared to men. In accordance with findings from LeResche et al, and Fink et al, we also found that women were more likely to report chronic health conditions including pain (17) and depression (14). …”
Section: Discussionsupporting
confidence: 92%
“…In the 2011–2012 cohort, (n= 113,665) analyzed using multinomial logistic regression for past year misuse of prescription opioids, misuse of prescription opioids and major depressive episodes (MDE) were prevalent among women but not for men (14). Additionally, poly-drug use was found to be more prevalent among those with comorbid misuse of prescription opioids and MDE than persons with prescription opioid misuse alone or MDE alone.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, in this study, the central theme that emerged was that polydrug abuse is predominantly associated with Twitter prescription drug abuse discussions and could be indicative of larger behavioral trends of users abusing multiple prescription drugs and also combining use with other illicit substances. These results could form the basis for future indepth studies examining the unique health and substance abuse consequences associated highly prevalent polydrug uses (including potentially linkages to mental health issues and behavior among young adults and adolescents already identified in the literature) (Fink et al, 2015;Kelly, Wells, Pawson, LeClair, & Parsons, 2014;Mackesy-Amiti, Donenberg, Ouellet, 2015).…”
Section: Resultsmentioning
confidence: 81%
“…56 This study found association between low income and 12-month MDD, consistent with other studies conducted within the last 3 years. 1,57,58 While this association could be due to depression-impaired functioning leading to lower income, the increases in depression and suicide that have accompanied growing income inequality suggest that the relationship of low income to MDD is due to stress from inadequate financial resources for life necessities or pessimism about improved future prospects. 1 If so, while treatment can benefit those with MDD, prevention may require change in larger societal processes.…”
Section: Discussionmentioning
confidence: 99%